Synovial fluid genexpert quietus diagnostic jostle – A case report and algorithmic approach to monoarthritis - Prajna Karki; Ramyasri Kodali; Vineeta shobha (Indian Journal of Rheumatology)
Owing to the difficult anatomy, difficulty in procuring tissue samples, and clinical mimicry, the diagnosis of extrapulmonary, especially osteoarticular tuberculosis (TB), remains a challenge. Arriving at the correct diagnosis of articular TB frequently requires synovial biopsy and synovial fluid or tissue culture. Efficient utilization of rapid molecular assays such as Xpert Mycobacterium tuberculosis (MTB)/RIF assay can support the timely and accurate diagnosis. Xpert® MTB/RIF (Xpert) is a rapid, automated, nucleic acid amplification assay, recommended by the World Health Organization for the simultaneous detection of MTB complex and rifampicin resistance. Here, we report the case of long-standing inflammatory monoarthritis wherein the diagnosis took a protracted course. This case is reported to highlight that the employment of highly specific modern diagnostic technologies which are available through the Revised National TB Control Program results in swift and accurate diagnosis.